Validation of Vote Counting Supervision Based on Vote Tally at West Bangka District - Ekariva Annas, Asmara; Mochammad, Afiffudin; Tri Basuki, Kurniawan; Edi, Suryanegara (INTI International University, 2022)
In Indonesia, the supervision of regional head elections is carried out by the Election Supervisory Board (Bawaslu) and its staff. Bawaslu conducts supervision starting from the initial stage to the final stage. The mechanism for using the people's right to vote is carried out at the Voting and Counting Stages. In the 2020 Regional Head Elections, the General Election Commission uses the SIREKAP system (Electronic Recapitulation Information System) in the calculation of SIREKAP. According to the author, there are still problems, one of which is a manual summation, calculation errors, and input errors. On the Model C Form, the results of the KWK vote tally are calculated manually, then the officer adds up the tally and enters it into the SIREKAP. Supervision of Vote Count Recapitulation is an urgent matter because supervision is a comparison of vote acquisition results which can prevent manual summation errors on Form Model C and Results-KWK. The author proposes a validation method for monitoring vote counting using an artificial neural network approach. With this method, the sum is done from Tally's votes.